Exploring Unbalanced Growth Theory by Linear and Nonlinear Methods: Case of Indonesia - Saliminezhad, Andisheh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This study seeks to test the Hirschman’s theory of unbalanced growth and the viability of adopting a nonlinear model in Indonesia. It also studies the growth pattern in Indonesia by employing a suite of variable ranking algorithms to find the most significant leading sector during the study period from 1995 to 2015. To this end, an Input-Output framework is applied to detect the high linkage sector(s) (key sectors) of the Indonesian economy. Then the linear and nonlinear relationships between the extracted key sectors and GDP growth are covered with two different approaches specifically, Multiple Linear Regression and Multi-Layered Perceptron (MLP) Artificial Neural Network (ANN). Whereas detection of sector ranking is crucial for preparing a proper development plan; in the same vein, we apply two types of feature ranking methods (namely, Stepwise Regression and Ant Colony Optimization (ACO)-MLP based). Empirical results from linear and non-linear models show that the effects of different sectors on growth in GDP in Indonesia are consistent with the structure of unbalanced growth theory. In general, we found that manufacturing sector is the most strategic sector in Indonesia since it has been selected both by linear and nonlinear forms as the first rank. Therefore, its development path firstly could be reinforced by more investment in this leading sector and then followed by investment in construction, hotels and restaurants, and agriculture.

ÖZ: Bu çalışmada, Hirschman’nın unbalanced kalkınma teorisi Endonezya için nonlinear model kullanılarak test edilmiştir. Bu çalışmada, 1995 ile 2015 arasında Endonesya’nın kalkınma trendini değişken sıralama algoritmaları paketi kulanılarak incelenmiş ve kanlınma için en önemli sektörler belirlenmiştir. Son olarak, girdi çıktı taploları kullanarak Endonezya ekonomisi için en önemli sektörler belirlemiştir. Ekonomik kalkınma ile başlıca sektörler arasındaki doğrusal ve doğrusal olmayan ilişkiyi incelemek için iki farklı yaklaşım kulanılmıştır basit doğrusal regresyon ve MLP yapay sinir ağı modelleri. Beklenen kalkınma palnı hazırlanabilmesi için sektorlerlerin önem listesinin belirlenmesi çok önemlidir, bu doğrultuda, iki farklı ranking tekniği kulanılmıştır (isimleri, Stepwise Regression and Ant Colony Optimization (ACO). Doğrusal ve doğrusal olmayan modellerin bilimsel sonuçları gösterimiştir ki Endonezyada farklı sektörlerin ekonomik kalkınmaya etkileri unbalance kalkınma theroisinin yapısı ile tutarlıdır. Genel olarak, imalat sektörü Endonesyadaki en stratejik sektör olarak seçilmiştir doğrusal ve doğrusal olmayan sıralama sonuçları sonrası. Böylelikle, ekonomik kalkınma ilk olarak bu sektöre yatırımdan geçmekte, diyer önemli sektörler sırasıyla, inşaat, hotel ve resotrant, ve tarımdır.
Doctor of Philosophy in Economics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2018. Supervisor: Prof. Dr. Fatma Güven Lisaniler.
Keywords: Economics; Economic development--Indonesia; Consumption (Economics)--Mathematical models--Capital stock--Mathematical models; Economic Development; Neural Networks; Input Output Analyses; Feature Selection Methods